2017
DOI: 10.1186/s13045-017-0393-3
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic stem cell transplantation in adult patients with acute myeloid leukaemia and 17p abnormalities in first complete remission: a study from the Acute Leukemia Working Party (ALWP) of the European Society for Blood and Marrow Transplantation (EBMT)

Abstract: BackgroundAcute myeloid leukaemia (AML) with 17p abnormalities (abn(17p)) carries a very poor prognosis due to high refractoriness to conventional chemotherapy, and allogeneic stem cell transplantation (allo-SCT) appears as the only potential curative option.MethodsTo address outcomes after allo-SCT in patients with abn(17p), we retrospectively analysed de novo or secondary AML undergoing SCT between 2000 and 2013 from the EBMT registry.ResultsOne hundred thirty-nine patients with confirmed abn(17p) have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 51 publications
7
30
0
4
Order By: Relevance
“…26 We also found that sAML was significantly associated with increased NRM and decreased OS as previously described, 27,28 So, -7/7q-is the most frequent cytogenetic feature reported as sole abnormality, 23 which is well illustrated within our population with 42% of the patients harboring -7/7q-without CK, MK, -5/5q-, abn (17p) and inv (3). As suggested by our previous dataset, 18 we hypothesized that the prognosis of our cohort would be dictated by the presence of additional adverse cytogenetic abnormalities. While CK did not show an impact on outcomes in multivariate analysis, we found a significantly worse survival in patients harboring MK, -5/5q-, abn(17p) and inv ( SCT in high-risk AML.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…26 We also found that sAML was significantly associated with increased NRM and decreased OS as previously described, 27,28 So, -7/7q-is the most frequent cytogenetic feature reported as sole abnormality, 23 which is well illustrated within our population with 42% of the patients harboring -7/7q-without CK, MK, -5/5q-, abn (17p) and inv (3). As suggested by our previous dataset, 18 we hypothesized that the prognosis of our cohort would be dictated by the presence of additional adverse cytogenetic abnormalities. While CK did not show an impact on outcomes in multivariate analysis, we found a significantly worse survival in patients harboring MK, -5/5q-, abn(17p) and inv ( SCT in high-risk AML.…”
Section: Discussionsupporting
confidence: 88%
“…38,39 Our "abn(17p)" group translated into a 2-year probability of LFS of only 19% if transplanted in CR1, which is worse than previously published data. 18,40 These worse results might be related to the presence of 66% -5/5q-within the "abn(17p)" group, which supports our previous observation of the deleterious effect of the combination of -5/5q-and abn(17p) on outcomes after SCT. 18 To further support the negative combinatorial impact of -5/5q-and abn(17p), we subsequently studied separately -5/5q-, abn(17p) and the combination of -5/5q-with abn(17p).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations